Using queuing theory to describe adaptive mathematical models of computing systems with resource virtualization and its verification using a virtual server with a configuration similar to the configuration of a given model - Alexey I. Martyshkin; Dmitry V. Pashchenko; Dmitry A. Trokoz; Mihail P. Sinev; Boris L. Svistunov (Bulletin of Electrical Engineering and Informatics, 2020)
The article describes the issues of preparation and verification of mathematical models of computing systems with resource virtualization. The object of this study is to verify of mathematical models of computer systems with virtualization experimentally by creating a virtual server on the host platform and monitoring its characteristics under load. Known models cannot be applied to the aircraft with virtualization, because they do not allow a comprehensive analysis to determine the most effective option for the implementation of the initial allocation of resources and its optimization for a specific sphere and task of use. The article for the study used a closed queueing network. Simple models for the analysis of various structures of computer systems are experimentally obtained. To implement the properties of adaptability in the models, triggers are used that monitor and adjust the power of the processing channel in individual Queuing systems, depending on the specified conditions. Experiments prove the obtained results reliable and usable as a flexible tool for studying the virtualization properties when structuring computing systems. This knowledge could be of use for businesses interested in optimizing the server configuration for their IT infrastructure.